Self-Esteem In Context: A Case Study of the Motivational Processes Underlying Social Identity Construction by Township Youth - Campbell, Catherine (PINS-Psychology in Society, 2026)
The issues examined in this paper are located within the context of the debate in Social Identity Theory (SIT) about the motivational forces underlying identity formation. The starting point of the paper is SIT in the tradition of Tajfel and Turner (Tajfel & Turner, 1979; Tajfel 1981, Hogg & Abrams, 1988). According to SIT, people are motivated by a fundamental need for self-esteem in the process of identity construction. Despite a fair amount of criticism (e.g. Abrams & Hogg, 1988; Hogg & Abrams, 1990), the "self esteem hypothesis" has received substantial empirical support. However much of this supporting empirical research has been conducted in experimental studies or laboratory conditions rather than in real-life social contexts (e.g. Hinkle & Brown, 1990; Hogg & Sunderland, 1991; Crocker, Blaine & Luhtanen, 1993). This paper reports on a research project which sought to address comments that SIT lacks ecological validity (Abrams, 1992; Hogg & Abrams, 1990; Reicher & Hopkins, 1996). The aim of this study was to complement SIT’s predominantly laboratory and experimental findings with research conducted in a non-laboratory context, investigating social identity formation within natural social groupings. Against this background, detailed open-ended interviews were conducted with 40 residents of a Durban township, aged between 17 and 23 years, in the interests of investigating the process of social identity construction in the rapidly changing social climate of the early 1990s prior to the release of Mandela. This paper presents a case study of the motivational processes underlying the social identity of this group of young people.